Detection of Candida albicans in Females Urinary Tract Infection by using Microscopical and Cultural Methods of Urine Samples in Kirkuk City - Iraq - Burhan A. Mohammed (Journal of Global Pharma Technology, 2016)
Background: Candiduria is an infectious condition worldwide distribution as a primary infection of human urogenital tract caused by Candida albicans predominantly. Increasing of urinary tract infections with Candida species has led to antifungal resistant conditions as a common problem of women specifically among pregnant women. This study is an attempt to show the incidence of Candida albicans among women attending gynecology clinical in Kirkuk General Hospital in Kirkuk city, by microscopically technique and urine inoculation into Sabouraud Dextrose Agar. Methods & Materials: In this study, one hundred and seventy-four midstream urine samples from women patients of gynecology clinical in Kirkuk General Hospital were collected. All the subjects were clinically assessed for studying C .albicans infection, and then inoculated on Sabouraud Dextrose Agar. Results: The highest percentage of infection of C. albicans was 38(52.8%) of the positive patients and in relation to the patients pregnancy status, C. albicans infection revealed a prevalence of 36(53.7%) higher than 2(40%) for the non-pregnant patients with abnormal general urine examination in age group 27-36 years respectively. Conclusions: The study revealed that the prevalence of Candidal urinary tract infections (UTIs) among the younger reproductive age of the pregnant women was higher than that of non-pregnant women and the Candida albicans was the most common Candida species causative agent of the urinary tract Candidiasis.  Keywords: C. albicans, Microscopical, Culture Methods, UTI.